Responda:
Por favor veja abaixo.
Explicação:
Deixei # 1 + costheta + isintheta = r (cosalpha + isinalpha) #, Aqui # r = sqrt ((1 + costheta) ^ 2 + sen ^ 2theta) = sqrt (2 + 2costheta) #
= #sqrt (2 + 4cos ^ 2 (teta / 2) -2) = 2cos (teta / 2) #
e # tanalfa = sineta / (1 + costheta) == (2sin (teta / 2) cos (teta / 2)) / (2cos ^ 2 (teta / 2)) = tan (teta / 2) # ou # alpha = theta / 2 #
então # 1 + costheta-isintheta = r (cos (-alfa) + isin (-alfa)) = r (cosalfa-isinalfa) #
e nós podemos escrever # (1 + costheta + isintheta) ^ n + (1 + costheta-isintheta) ^ n # usando o teorema de DE MOIVRE como
# r ^ n (cosnalpha + isinnalpha + cosnalpha-isinnalpha) #
= # 2r ^ ncosnalpha #
= # 2 * 2 ^ ncos ^ n (teta / 2) cos ((ntheta) / 2) #
= # 2 ^ (n + 1) cos ^ n (teta / 2) cos ((ntheta) / 2) #